1997
DOI: 10.1557/jmr.1997.0040
|View full text |Cite
|
Sign up to set email alerts
|

Lowering the formation temperature of the C54-TiSi2 phase using a metallic interfacial layer

Abstract: We demonstrate that the formation temperature of the C54 TiSi2 phase from the bilayer reaction of Ti on Si is lowered by approximately 100 °C by placing an interfacial layer of Mo or W between Ti and Si. Upon annealing above 500 °C, the C49 TiSi2 phase forms first, as in the reaction of Ti directly on Si. However, the temperature range over which the C49 phase is stable is decreased by approximately 100 °C, allowing C54 TiSi2 formation below 700 °C. Patterned submicron lines (0.25−1.0 μm wide) fabricated witho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

1997
1997
2003
2003

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…1. The second sharp decrease in resistance 6,9,29 corresponds to the C49-C54 transformation. The presence of Nb causes this second decrease to shift to-wards lower temperatures continuously with increasing Nb content.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1. The second sharp decrease in resistance 6,9,29 corresponds to the C49-C54 transformation. The presence of Nb causes this second decrease to shift to-wards lower temperatures continuously with increasing Nb content.…”
Section: Resultsmentioning
confidence: 99%
“…Adding small amounts of refractory metals ͑RM͒, either Ta, Nb, Mo, or W, to the Ti-Si binary system results in the formation of C54 TiSi 2 at temperatures 100°C-150°C lower than what is needed for the transformation with pure Ti-Si. The refractory metals can be implanted into the Si substrate prior to Ti deposition, 4 deposited as an interposed layer between Ti and Si, [5][6][7][8] or deposited together with Ti as an alloy, 9 as was done in the present study. The effect has been attributed to a template effect 5 due to the initial formation of still another phase with the C40 structure.…”
Section: Introductionmentioning
confidence: 99%
“…In the C54 structure with 10% Nb, the smallest unit, i.e., one metal and two Si atoms, occupies 0.0422 nm 3 . In the C40 structure with 20.5% Nb, the unit volume is only 0.0421 nm 3 . This indicates that when the crystallographic structure of disilicide changes from C54 into C40 with the Nb content increasing from 10% to 20.5% at the metal sites, the cell volume undergoes a discontinuity.…”
Section: Resultsmentioning
confidence: 99%
“…The transformation temperature is reduced by small quantities of refractory metal, such as Mo, Ta, Nb, or W, introduced at or near the Ti/Si interface. 5,7,11,13 Earlier work also showed that the C49 grain size of blanket Ti films on ͗100͘ Si can be reduced, and the transformation temperature lowered, by increasing the ramp rate of the first RTP. 12 More recent work showed that higher ramp rates result in lower sheet resistance for deep submicron lines.…”
Section: Introductionmentioning
confidence: 96%
“…In order to extend Tisalicide manufacturing to deep submicron applications there have been many studies of the C49 to C54 transformation. [3][4][5][6][7][8][9][10][11][12][13][14][15][16] The transformation temperature has been shown to be a function of film thickness, 6,17 C49 grain size, 12 dopants in the Si, 3 and other factors. The transformation temperature is reduced by small quantities of refractory metal, such as Mo, Ta, Nb, or W, introduced at or near the Ti/Si interface.…”
Section: Introductionmentioning
confidence: 99%